The effects of behavioural obesity treatment in Iceland with or without surgical intervention on weight loss, body composition, physical work capacity and physical activity: A 4-year follow-up - Guðlaugur Birgisson 1970- (2014)
Background Obesity is one of world’s largest health problems. Since 2001, the Reykjalundur Rehabilitation Centre in Iceland has utilized multidisciplinary obesity treatment involving a behavioural approach for severely obese patients (BMI ≥ 35 kg/m²) with possible pairing with Laparoscopic Roux-en-Y gastric bypass (LRYGB). Aims The main aim of this 4-year follow-up study is to investigate the outcome of severely obese patients after undergoing behavioural obesity treatment at Reykjalundur as well as to identify any interaction between surgical treatment status (LRYGB or not) and the success of the behavioural obesity treatment. Methods In this observational longitudinal study, subjects’ bodyweight, body mass index (BMI), waist circumference, body composition, maximal physical work capacity on an ergometer cycle, and regular physical activity were recorded at the beginning of treatment (in years 2006-2008) and at a 4-year follow-up appointment. Patients non-randomly (by their own choice) received behavioural treatment alone (treatment group) or behavioural treatment plus gastric bypass surgery (treatment with surgery group). Results Ninety of 120 (75%) eligible candidates participated, including 9 men and 81 women with a mean age of 40.3 years. Forty-seven patients (52%) underwent gastric bypass surgery. Both groups had significant (p<0.05) reductions in bodyweight, BMI, waist circumference, fat mass (FM), and fat percentage at 4-year follow-up. Both groups also increased their levels of physical activity. However the treatment with surgery group subjects had better results in most outcomes than non-surgically treated subjects. Maximal physical work capacity per weight (W/kg) increased in the treatment with surgery group (p<0.05) but remained unchanged in the treatment group. Conclusion Behavioural obesity treatment was shown to be an effective therapeutic technique for severely obese patients, as patients showed significant improvements in BMI, waist circumference, body composition, and physical activity ...